2020
DOI: 10.4046/trd.2020.0003
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Molecular Basis of Lung Aging and Its Associated Diseases

Abstract: Aging is often viewed as a progressive decline in fitness due to cumulative deleterious alterations of biological functions in the living system. Recently, our understanding of the molecular mechanisms underlying aging biology has significantly advanced. Interestingly, many of the pivotal molecular features of aging biology are also found to contribute to the pathogenesis of chronic lung disorders such as chronic obstructive pulmonary disease and idiopathic pulmonary fibrosis, for which advanced age is the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…It is a major challenge to elucidate how scientific advances in molecular insights of aging biology can be integrated into a conceptual framework that will illuminate the mechanistic understanding of lung aging and its related disorders (Budinger et al, 2017). Besides, the body of scientific knowledge related to lung aging and its contribution to the pathobiology of chronic lung diseases is lagging far behind other recent advances in aging biology (Kang, 2020). Regarding this, we previously reported that, from three independent human COPD cohorts, the expression of NLRX1 was suppressed in the lungs from patients with COPD and this suppression showed a strong correlation with the degree of airflow limitation, a hallmark of COPD (Kang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a major challenge to elucidate how scientific advances in molecular insights of aging biology can be integrated into a conceptual framework that will illuminate the mechanistic understanding of lung aging and its related disorders (Budinger et al, 2017). Besides, the body of scientific knowledge related to lung aging and its contribution to the pathobiology of chronic lung diseases is lagging far behind other recent advances in aging biology (Kang, 2020). Regarding this, we previously reported that, from three independent human COPD cohorts, the expression of NLRX1 was suppressed in the lungs from patients with COPD and this suppression showed a strong correlation with the degree of airflow limitation, a hallmark of COPD (Kang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported the pathogenic role of NLRX1, which may contribute to the development of chronic obstructive pulmonary disease (COPD) (Kang et al, 2015). Additionally, there is growing evidence that aging hallmarks are noticeable features of COPD (Easter et al, 2020;Kang, 2020). Indeed, when we assessed the level of NLRX1 expression with normative aging in murine lungs, both mRNA and protein expression levels of NLRX1 were significantly reduced in 12-and 24-month-old (mo) mice compared with those of young (3-months) mice (Figure 5a-c and Figure S1a,b).…”
Section: Nucleotide-binding Domain and Leucinerich-repeat-containing Protein X1 Decreases With Normative Aging And Aging Lung-like Changementioning
confidence: 99%
“…Calorie restriction (CR) diets have proven to be beneficial in combating disorders such as pulmonary fibrosis, which is linked to oxidative stress and old age [ 191 , 192 ]. In order to elucidate the effects of the CR diet on oxidative stress, Qui et al.…”
Section: Events In Ipf Hdacs Tgf-β Signalling and Therapeuticsmentioning
confidence: 99%
“…Increased TGF-β signalling decreases SIRT3 levels, resulting in increased levels of acetylated SOD2 followed by a rise in oxidative stress that is favourable for FMD [179,189]. Calorie restriction (CR) diets have proven to be beneficial in combating disorders such as pulmonary fibrosis, which is linked to oxidative stress and old age [191,192]. In order to elucidate the effects of the CR diet on oxidative stress, Qui et al fed CR diet to Sirt3 knockout mice and also to their wild-type counterparts.…”
Section: Formation Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…By demonstrating that bleomycin injury-induced cellular senescence is significantly attenuated in a MAVS-dependent manner, our study may provide additional mechanistic insight of how MAVS contributes to the development of pulmonary fibrosis. The significance of these novel observations should be explored in future studies, considering that cellular senescence has emerged as a crucial driving force of IPF pathogenesis [25,26,38].…”
Section: Discussionmentioning
confidence: 99%